Amos Oz : The Legacy of a Writer in Israel and Beyond. - Omer-Sherman, Ranen (State University of New York Press, 2023)
Explores the writer's enduring literary and political legacy.
Description based upon print version of record.
Keywords: Oz, Amos, -- 1939-2018 -- Influence.; Oz, Amos, -- 1939-2018 -- Criticism and interpretation.; Oz, Amos, -- 1939-2018; Israeli literature -- History and criticism.; Israeli literature -- Political aspects.; Littérature israélienne -- Histoire et critique.; Littérature israélienne -- Aspect politique.; LITERARY CRITICISM / Jewish.; Influence (Literary, artistic, etc.); Israeli literature; Israeli literature -- Political aspects; Criticism, interpretation, etc.; Literary criticism.; Critiques littéraires.